2017
DOI: 10.1096/fj.201601348r
|View full text |Cite
|
Sign up to set email alerts
|

N‐acetylcysteine accelerates amputation stump healing in the setting of diabetes

Abstract: Over 60% of lower extremity amputations are performed in patients with diabetes and peripheral arterial disease, and at least 25% require subsequent reamputation due to poor surgical site healing. The mechanisms underlying poor amputation stump healing in the setting of diabetes are not understood. -acetylcysteine (NAC) is known to promote endothelial cell function and angiogenesis and may have therapeutic benefits in the setting of diabetes. We tested the hypothesis that NAC alters the vascular milieu to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 51 publications
1
28
0
1
Order By: Relevance
“…Propolis could increase the glutathione (GSH) and GSH/glutathione disulfide (GSSG) ratio, deplete TNF, and increased interleukin10 levels to reduce the wound area [ 108 ]. Antioxidant with N -acetyl cysteine (NAC) is known to improve endothelial cell function and angiogenesis, and Mohamed et.al reported that daily NAC use improved postamputation stump healing, perfusion, neovascularization, and reduced muscle fiber damage [ 109 , 110 ] ( Table 1 ).…”
Section: Antioxidants In Diabetic Wound Healingmentioning
confidence: 99%
“…Propolis could increase the glutathione (GSH) and GSH/glutathione disulfide (GSSG) ratio, deplete TNF, and increased interleukin10 levels to reduce the wound area [ 108 ]. Antioxidant with N -acetyl cysteine (NAC) is known to improve endothelial cell function and angiogenesis, and Mohamed et.al reported that daily NAC use improved postamputation stump healing, perfusion, neovascularization, and reduced muscle fiber damage [ 109 , 110 ] ( Table 1 ).…”
Section: Antioxidants In Diabetic Wound Healingmentioning
confidence: 99%
“…NAC may have a broader therapeutic potential, particularly in the setting of antioxidants 35. Recently, Zayed et al observed that NAC could accelerate amputation stump healing by increased neovascularization casting new light on its use in wound healing 36. Besides, NAC can reduce the ROS level of the injured area, thus protecting the functional cells from the damage caused by excessive ROS 37.…”
Section: Introductionmentioning
confidence: 99%
“…Özkaya et al (2019) demonstrated that both topical (300 mg/kg for 14 days) and systemic (200 mg/kg for 14 days) treatment with NAC accelerates wound healing due to its positive effects on oxidative stress parameters in tissue and serum in diabetic rat models. Zayed et al (2017) showed that NAC (150 mg/kg for 7 days) accelerates wound healing by increasing proliferation and reducing inflammation through perfusion and palmitoylation signalling of phospholipase Cβ and Gαq in endothelial cells under ischemic conditions in the STZ-induced diabetes model. On the other hand, Tsai et al (2014) have reported that at the relatively lower doses than other studies various NAC concentrations (0.1, 0.5, and 1.0 mM) increased glutathione levels, cell viability, scratch-wound healing activities and migration abilities of CCD-966SK cells after 24 hours in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative mechanism may be the induction of epithelial cell proliferation. Zayed et al (2017) showed that NAC (150 mg/kg for 7 days) accelerates wound healing by increasing perfusion and proliferation under ischemic conditions in mice with STZinduced diabetes, suggesting that NAC increases the proliferation of endothelial cells through phospholipase Cβ signalling. In another study, it was reported that NAC inhibits inflammatory factors and facilitates epidermal proliferation via NF-B (Samuni et al, 2013).…”
Section: Discussionmentioning
confidence: 99%